Irrigation frequency, crop development and yield of Kidney bean - Resende, Morethson; Henderson, Delbert W.; Fereres, Elias (Pesquisa Agropecuaria Brasileira, 2014)
The effects of high frequency deficit irrigation on plant water status, leaf growth, dry matter accumulation, leaf resistance, photosynthesis rate and yield of Dark-Red kidney bean were studied by using line-source sprinkler irrigation on a "Yolo" soil at Davis, California, in 1977 and 1978. Aiming at different degrees of plant water stress at each frequency, the amount of water applied in the different treatments as a percentage of evapotranspiration varied. Leaf resistance and photosynthetic rate were not affected by irrigation regimes nor by the degree of stress. On the other hand, source size, total dry matter and yield were reduced about the same proportion as the reduction on ET, independently of the irrigation frequency. No advantage was found by using high frequency irrigation as compared with normal.